(untitled) (Innovative professional education, 2024)
In the conditions of the large-scale invasion of the Russian Federation on the territory of Ukraine, the destruction of the stable economic system, there is a growing need for qualified workers who have entrepreneurial skills and the ability to effectively organize their own business. Internally displaced persons are one of the most vulnerable social groups in the conditions of armed conflict and deep economic crisis in Ukraine. One of the ways of their socio- economic integration into the host communities is to start their own business. The article highlights the main areas of educational activity for the development of entrepreneurial skills among the adult population of internally displaced persons.